Payments under the Common Agricultural Policy as a determinant of development of different types of agricultural holdings = Płatności WPR jako determinanta ekonomiczna rozwoju różnych typów gospodarstw rolnych - Czyżewski, Andrzej; Kryszak, Łukasz (Zielona Góra: Faculty of Economics and Management Press)
The main aim of this article was to investigate the influence of payments under the CAP on economic development of different types of farms. The main source of data was FADN database. A period of research covers the years of 2004-2013.The article referred to previous results of research in the field of payments and its role for the economic situation of agricultural holdings.
Keywords: WPR; dochody rolnicze; akumulacja; rentowność kapitałów własnych; dochodowość gospodarstw; CAP; agricultural income; accumulation; Return on Equity; farm profitability